You belong to me - Clark, Mary Higgins; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 2012)
A beautiful and dedicated young psychoanalyst is terrified to discover that her beloved sister is determined to marry one of the doctor's former patients, a man who conceals a dangerously jealous, obsessive nature, as well as a pattern of abuse, behind his charming and wealthy facade.
Originally published: New York : Simon & Schuster, 1998.
Keywords: Women -- Crimes against -- Fiction; Serial murderers -- Fiction; Radio talk shows -- Fiction; Cruise ships -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction